Green alga-mediated treatment process for removal of zinc from synthetic solution and industrial effluent. Issue 10 (29th April 2019) - Senthilkumar, R.; Prasad, D. M. Reddy; Govindarajan, L.; Saravanakumar, K.; Prasad, B. S. Naveen
ABSTRACT: The present work explored biosorption of Zn(II) ions from aqueous and zinc-bearing factory effluent using marine seaweed Ulva lactuca . The batch pH edge experiments using aqueous zinc solution indicated that Zn(II) uptake by U. lactuca was found to be maximum at pH 4.5 and the batch isotherm trials performed at pH 4.5 resulted in maximum uptake capacity of 128.0 mg Zn(II)/g. With 0.1 M CaCl2 (pH 3.5, HCl) as elutant, the elution of Zn(II) ions from Zn(II)-laden U. lactuca biosorbent was effective with possible regeneration and reuse for three cycles. The zinc industrial effluent was found to comprise of 87.8 mg/L of zinc ions along with excess co-ions and high total dissolved solids (838.1 mg/L). Owing to this, Zn(II) uptake from electroplating effluent by U. lactuca was suppressed due to competition from other ions. Continuous-flow sorption trials were conducted at flow rate of 5 mL/min in an up-flow fixed column. The existence of surplus competing ions in zinc wastewater influenced the Zn(II) biosorption by U. lactuca . U. lactuca -loaded packed column exhibited uptakes of 78.3 and 70.8 mg Zn(II)/g for aqueous solution and effluent, respectively. The results of three continuous sorption–desorption cycles demonstrated that reuse of U. lactuca biosorbent in remediation of zinc-containing wastewaters was practical and economical.